Nature technology : creating a fresh approach to technology and lifestyle - Ishida, Emile H. (Springer Japan, 2013)
The Great East Japan Earthquake, which occurred on March 11, 2011, reminded us that we were just one species within the great cycle of life on earth, that we were allowed to survive only because of nature, and that the idea that we were somehow able to conquer nature was simply an illusion. Now more than ever it is time that we confront head-on the change from the "underground resources" type of civilization to one with a new way of life and technology that embraces a sense of nature. To do so, we must learn from nature, the only sustainable society on earth, and create technology that embraces such a view of nature. We call such technology, which cleverly revives nature's greatness, Nature Technology. Taking a casual glance at nature, a nest of termites in the savanna region can be observed to maintain a steady temperature of 30°C despite the fact that the outside air temperature ranges from 50°C during the day to nearly 0°C at night. There are countless numbers of open pores just several billionths of a meter (nanometer) wide in the "earth" of the nest, which serve to regulate the temperature and humidity. In fact, all kinds of "earth" have these pores (clay mineral with aggregated structures) and air conditioners that require no electricity have been created by hardening this earth while preserving its structure; a cooling floor or wall becomes the alternative to a conventional air conditioner. This book provides many such examples of how Nature Technology can support a new lifestyle that is both environmentally sound and spiritually uplifting.